Caractéristiques de l’évolution spatio-temporelle de Pectinophora gossypiella Saunders (Lepidoptera : Gelechiidae) dans les zones de production cotonnière de Côte d’Ivoire : Implications pour une stratégie de gestion optimale de la résistance aux pyréthrinoïdes - Ochou, Germain Elisabeth Cynthia; Kobenan, Koffi Christophe; Kone, Pitou Woklin Euloge; Didi, Roland; Kouakou, Malanno; Bini, Kouadio Kra Norbert; Mamadou, Dagnogo; Dick, Acka Emmanuel; Ochou, Ochou Germain (European Scientific Journal, ESJ, 2018)
In order to update knowledge on the spatio-temporal evolution of Pectinophora gossypiella, the geographical areas and the seasons of predilection of adult and larval populations have been studied in the last six years from 2012 to 2017. The study showed that adult populations are more abundant in the cotton production area of the South compared to the North. They have a very low activity during the intercropping season while the most important outbreaks occurred in October-December. The monitoring of larval populations carried out on farm scale showed that infestations started on cotton early August and increased until November, which leads to a strong relationship between the evolution of adult populations, larval infestations and cotton plant phenology. Late sowings D5 and D6 exhibited higher levels of infestation (0.50 to 0.80 larvae/100 bolls) as compared to early sowing (0.21-0.31 larvae/100 bolls). Annual variations of pest infestation levels increased from years to years, fluctuating from 0.14 to 0.95 larvae/100 bolls over the study period. Mapping of the geographic distribution of infestation showed more severe pest pressure in the southern cotton areas, mostly in surrounding areas of Bouaké, Bouaflé, Séguéla and Boron (18,90; 5,33; 1,52; 1,06 larvae/100 bolls respectively). With regard to the emerging status of P. gossypiella over recent years, the current pyrethroid resistance management strategy deserves to be improved on the basis of the pest geographic and seasonal profiles.